The essence and functions of money and money transactions in the works of Baroque literature (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
The paper deals with the function of money in the Baroque period. It analyzes the works of Baroque Ukrainian writers and identifies the essence of money, money transactions, and the attitude of authors to them. Aspect analysis of the great deal of works dated by that period shows that during the 17th and 18th centuries for a Baroque person money used to be the sign of earthiness and connivance. However in the middle of the 18th century in the works the writers the image of money and related operations becomes different. This idea can be proved by the works of V. Hrygorovych-Barskyi and H. Skovoroda. The acute need for money was constantly felt by pilgrims, because for them money was the means of survival during their travels. In the works of the writers of the 18th century, the image of the fair, the merchant, is increasingly rising as well as the implementation of various monetary operations.
Keywords: money; baroque; purchase / sale; economic relations; means of survival; accumulation; money transactions